The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1590/1678-6971/eramf210007
|View full text |Cite
|
Sign up to set email alerts
|

Is Accounting Alchemy Still the Right Medicine for Firm’s Earnings and Book Value? Evidence From Sub-Saharan Africa

Abstract: Purpose: A major thread in accounting literature, which has remained a contentious issue, is how accounting alchemy can be modeled. The paper builds on existing accrual models in proposing an accounting alchemy model and tests if it is still the right medicine for earnings and book value of firms. The accounting alchemy model was based on mechanisms of earnings, book value, earnings before extraordinary items, net profit after tax, cash flow from operations, revenue, and total assets. We modified accrual mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…First, the study found no statistical problem with the data obtained as observed from the descriptive and diagnostic statistics see Tables 3-7. Second, we found that Pearson r for co-worker-incivility and supervisorincivility were negatively linked, thus indicating a negative link between workplace incivility (co-worker and supervisor incivilities) and employees' satisfaction; however, this result does not connote any statistical problem, since the Pearson r values were not above 0.8 as recommended by Gujarati (2003) cited in Okoro and kwueme (2021) and Okoro and Ihenyen (2020).…”
Section: Discussionmentioning
confidence: 51%
“…First, the study found no statistical problem with the data obtained as observed from the descriptive and diagnostic statistics see Tables 3-7. Second, we found that Pearson r for co-worker-incivility and supervisorincivility were negatively linked, thus indicating a negative link between workplace incivility (co-worker and supervisor incivilities) and employees' satisfaction; however, this result does not connote any statistical problem, since the Pearson r values were not above 0.8 as recommended by Gujarati (2003) cited in Okoro and kwueme (2021) and Okoro and Ihenyen (2020).…”
Section: Discussionmentioning
confidence: 51%
“…This suggests that there is a positive relationship between the market-level performance indicators (mbvr and tobinq) and the directors' observable characteristics. The correlation coefficients showed that no two directors' observable characteristics were perfectly correlated for the sampled firms in Nigeria and South Africa since none of the coefficients were above 0.8 (Gujarati, 2003cited in Okoro, 2014Okoro & Ekwueme, 2021;Imasuen, Okoro & Yahaya, 2022); hence, there is absence of multicollinearity problem in the empirical model of board of directors' observable characteristics and market-level financial performance. The mean VIF in Table 5 is 1.09 and is not above the accepted mean VIF level of 10, suggesting the nonexistence of multicollinearity problems in the empirical model of the directors' observable characteristics and market-level financial performance in Nigeria and South Africa.…”
Section: Resultsmentioning
confidence: 93%
“…The mean VIF is = 1.66 and is not greater than the accepted mean VIF of 10.0, indicating that there is an absence of multicollinearity problems in the models of workplace nepotism and employees' job satisfaction. VIF value above 10.0, according to Gujarati (2003), as cited in Egberi (2011); Okoye, Okoro and Salubi (2017); and Okoro and Ekwueme (2021), is considered good. Hence, the dataset is exceptionally reliable for conducting inferential statistics (multiple regressions).…”
Section: Methodsmentioning
confidence: 99%